The regional challenges affecting Kuwait's national security - Adnan Alenezi (Review of Economics and Political Science (REPS), 2020)
Purpose - This study aims to scrutinize and analyze the regional challenges facing Kuwait and their impact on Kuwait's national security since the outbreak of Arab Spring revolutions in 2011. These challenges are as follows: the Iranian threat, the Arab Spring revolutions and the recent Gulf crisis with Qatar. Design/methodology/approach - The study adopts national interest approach, which focuses on a state's economic, military and cultural objectives. According to this approach, a state seeks to achieve its own national interests. There are multiple national interests, but the ultimate goal is the survival and security of the state. Findings - The study concludes that the Gulf countries, including Kuwait, are facing unprecedented challenges as a result of the dire consequences of the Arab Spring revolutions, the control of Houthi group on Yemen's institutions and the repercussions of negotiations between 5 + 1 group (Russia, China, France, Britain, the USA + German) and Iran on the Iranian nuclear program. These developments are not in the interest of the Gulf countries in general and Kuwait in particular. The study recommends that Kuwait must adopt an external strategy based on achieving the regional balance with the countries of the region and dealing with different challenges according to its national interest. Originality/value - The importance of the study stems from the fact that the Arab region witnessed many developments at the political, economic and social levels since the outbreak of the Arab Spring revolutions. These developments posed many threats to Arab countries such as the spread of terrorism, religious extremism, terrorist organizations and non-state actors. They also became a key determinant of foreign policy. Kuwait was affected by these developments. In addition, it faces threats affecting its national security such as the Iranian threat, the Arab Spring revolutions and the Gulf crisis with Qatar. The study addresses these threats and how Kuwait, as a small state, has dealt with such enormous ones.
Keywords: 330; Iran; Kuwait; National security; The Gulf crisis; The Gulf region; The Iranian challenge